Minimally Displaced Lateral Humeral Condyle Fractures: Optimizing Follow-up and Minimizing Cost. Issue 1 (31st January 2023) - Kraft, Denver B.; Moore, Theresa J.; Pargas, Carlos; Rogers, Kenneth; Thacker, Mihir M.
Abstract : Background: Minimally displaced fractures of the lateral humeral condyle (LHC) may be treated nonoperatively in a long arm cast, but there is not a standardized evidence-based protocol. The aim of this study was to evaluate our nonoperatively treated LHC fractures, determine the risk of subsequent displacement, analyze our practice variability, and develop an evidence-based protocol to safely manage children with LHC fractures and to evaluate potential savings related to this analysis. Methods: We retrospectively reviewed clinical and radiographic parameters of all patients with LHC fractures at our institution from 2009 to 2015. All patients treated nonoperatively initially were included. We recorded demographic data and calculated the number of visits, casts applied, and radiographs within the first 4 weeks. We also analyzed practice variation among 27 treating providers. The number of children with subsequent displacement needing operative fixation was determined. We also looked at the average duration for each follow-up visit and the charges/costs associated with casting and radiographs. Results: There were 271 children with LHC fractures treated nonoperatively. Twenty-one were excluded because of the lack of adequate radiographs. There were 157 boys and 93 girls (average age 6.7 y). According to the Jakob classification, fracture types were as follows: 1 (230), 2 (20), and 3 (0). Within the first 4 weeks, the average number of visits was 2.6 (range: 1 to 5), average number of casts was 2.4 (range: 1 to 4), and the average number of radiographs was 9.4 (range: 2 to 31). Only 3 patients with LHC fracture type Jakob 1 were taken to the operating room post injury (9, 12, and 15 d, respectively) for subsequent displacement. Conclusion: Displacement in appropriately selected LHC fractures treated nonoperatively was rare (3/250, 1.2%) in this cohort, and the data question the need for multiple visits and radiographs in the first 4 weeks. Optimal follow-up (proposed follow-up at 10 to 15 d after injury and then 4 to 6 wk with radiographs, including an internal oblique view) would be safe, minimize waste, and result in better value-based care. Level of Evidence: Level IV.